Multiple infections containing the top five prevalent HPV genotypes and their impact on cervical lesions in Changzhou, China - Ping Gong; Bingwei Shi; Xing Cong; Liu Yang; Chunxiang Gong; Yilan Zhou; Xiaohong Li; Juan Wang (Taylor & Francis Group, 2023)
Human papillomavirus (HPV) infection is the primary cause of cervical cancer and its precursor lesions. The overall prevalence of HPV genotypes in Changzhou has previously been reported. However, the distribution of multiple HPV infections and their roles in cervical injury have less been investigated. We aimed to assess the prevalence of multiple HPV infections among the people in Changzhou. Furthermore, we analyzed whether multiple HPV infections comprising the top five prevalent HPVs were more associated with abnormalities in E6 and E7 (E6/E7) mRNA, liquid-based cytology, and cervical histopathology than a single infection. In the current study, HPV 16, 52, 58, 53, and 81 were the top five prevalent HPV types, both in single and multiple infections. Compared to a single infection, multiple infections containing HPV 16/52/58 were closely linked to positivity for E6/E7 mRNA. In addition to HPV 16, multiple infections containing the remaining top four HPVs conferred a significant advantage on atypical squamous cells of undermined significance or worse in comparison to a single infection. Furthermore, women with multiple infections containing the top five prevalent HPV types were more likely to develop cervical intraepithelial neoplasia grade II or worse than those with a single HPV infection. Our results demonstrate the superiority of multiple HPV infections containing the top five prevalent HPV types in cervical disease progression, which should be closely monitored. These findings are conducive for formulating regional preventive strategies for cervical cancer screening and vaccination in Changzhou.